2015
DOI: 10.3390/ma8105363
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Chemical Reduction of Reduced Graphene Oxide and Its Photocatalytic Activity in Degrading Reactive Black 5

Abstract: Textile industries consume large volumes of water for dye processing, leading to undesirable toxic dyes in water bodies. Dyestuffs are harmful to human health and aquatic life, and such illnesses as cholera, dysentery, hepatitis A, and hinder the photosynthetic activity of aquatic plants. To overcome this environmental problem, the advanced oxidation process is a promising technique to mineralize a wide range of dyes in water systems. In this work, reduced graphene oxide (rGO) was prepared via an advanced chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 41 publications
6
38
0
Order By: Relevance
“…It is observed that the pristine GO sheets show plane structure due to the presence of oxygen functional groups, whereas the ion irradiated GO sheets show layered structure. The GO sheets irradiated with 1 Â 10 14 ions/cm 2 shows less layered structure, which might be due to the insufficient fluence to remove the oxygen functional groups that attached at the edge and basal plane of GO layers [27]. However at high fluence, more number of oxygen removed from GO sheets, as evidenced from the RRBS measurement, hence the more layered structure is seen in GO sheets irradiated with 1 Â 10 16 ions/cm 2 .…”
Section: Resultsmentioning
confidence: 92%
“…It is observed that the pristine GO sheets show plane structure due to the presence of oxygen functional groups, whereas the ion irradiated GO sheets show layered structure. The GO sheets irradiated with 1 Â 10 14 ions/cm 2 shows less layered structure, which might be due to the insufficient fluence to remove the oxygen functional groups that attached at the edge and basal plane of GO layers [27]. However at high fluence, more number of oxygen removed from GO sheets, as evidenced from the RRBS measurement, hence the more layered structure is seen in GO sheets irradiated with 1 Â 10 16 ions/cm 2 .…”
Section: Resultsmentioning
confidence: 92%
“…Nevertheless, there are still some limits to the use of these scaffolds. First, inorganic materials are much harder to degrade, especially bulk materials, which could limit their clinical application. Second, these materials are usually bulk structures that are typically opaque inside the structure so that they have poor light transmission properties, making in situ imaging difficult …”
Section: Scaffold Biomaterials For 3d Culture Of Stem Cellsmentioning
confidence: 99%
“…Red-to-near-infrared PL emitted from chemically-reduced GO has been reported, consistent with increasing disorder length scale with reduction [7]. The rGO has been widely applied in energy storage devices, photovoltaics devices, corrosion protection, and lubricants [8]. In this study, we are investigating the optical properties of rGO prepared from old coconut shell using photoluminescence (PL) spectroscopy.…”
Section: Introductionmentioning
confidence: 66%